ASB17 Facilitates the Burst of LPS-Induced Inflammation Through Maintaining TRAF6 Stability - Wan, Pin; Yang, Ge; Zhang, Simeng; Zhang, Yaru; Jia, Yaling; Che, Xu; Luo, Zhen; Pan, Pan; Li, Geng; Chen, Xulin; Zhang, Qiwei; Zhang, Wen; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
ASB17, a member of the ankyrin repeat and SOCS box-containing protein (ASB) family, has been supposed to act as an E3 ubiquitin ligase. Actually, little is known about its biological function. In this study, we found that ASB17 knocking-out impaired the expression of the pro-inflammatory cytokines CCL2 and IL-6 in bone marrow-derived dendritic cells (BMDCs) stimulated by lipopolysaccharide (LPS), indicating an inflammation-promoting role of this gene. We reveal that ASB17 promotes LPS-induced nuclear factor kappa B (NF-κB) signal activation through interacting with TNF receptor-associated factor 6 (TRAF6) which is a crucial adaptor protein downstream of toll-like receptors (TLR). ASB17 via its aa177–250 segment interacts with the Zn finger domain of TRAF6. The interaction of ASB17 stabilizes TRAF6 protein through inhibiting K48-linked TRAF6 polyubiquitination. Therefore, we suggest that ASB17 facilitates LPS-induced NF-κB activation by maintaining TRAF6 protein stability. The inflammation enhancer role of ASB17 is recognized here, which provides new understanding of the activation process of inflammation and immune response.